Knowledge and practice on the preventive measures of bird flu among the poultry workers of Kathamndu valley. - Shrestha, Kripa (2009)
ABSTRACT: The flu caused by the virus H5N1 is simply referred as Bird flu. Bird flu were not only limited to Birds but also it threats the life of human beings. Nepal has also encountered the case of bird flu. There was the practice of importing chickens in poultry farm from outside the valley which may act as the risk factor of exposures. This research was conducted to know the knowledge and practice of poultry workers regarding the preventive measures of bird flu and to identify its gaps This study was carried out from May to Aug 2009 with the objective to determine the knowledge and practices on the preventive measures of bird flu among the poultry farmers of Kathmandu district. During the study 68 poultry workers were involved from Kathmandu, Lalitpur and Bhaktapur districts.Data collection tools were semi structured questionnaire and observational checklist and the techniques used were face to face interview and observational method. The study population varies from 15-54 and 1/3rd of the participants were female. There were significance association between knowledge and residence (P=0.021, OR=4.181), knowledge and occupation as owner (P=0.004, OR=5.963), knowledge and occupation as worker (P=0.004, OR=0.168).In case of practice, there were significance association between practice and gender (P=0.004, OR=4.615), practice and residence (P=0.004, OR=0.204), practice and occupation (as owner (P=0.00, OR=0.094) and worker (P=0.00, OR=10.689). The poultry workers were not fully safe; they were still vulnerable of Bird flu. Their knowledge as well as practices regarding the preventive measures was not sufficient. There is a huge gap between the knowledge and practices of preventive measures of Bird flu. This gap can be bridge by the proper orientation, demonstration, training of preventive measures